PENINGKATAN KINERJA MELALUI KEPEMIMPINAN, BUDAYA, DAN KOMPENSASI - Wahyudi Wahyudi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
It is not easy to get the best results consistently, because employee performance has limits. However, the company can maintain it, by presenting good leaders, encouraging the strengthening of a humanist work culture, and providing appropriate compensation, as a reward for the performance given. In fact, this research was conducted to see the causal relationship mathematically, so that the possible value of improving performance is known. The research method uses a survey with a questionnaire as a research instrument. The number of samples as many as 160 respondents, and the technique of taking it using a simple random sample. The results of the study confirm that employee performance is very sensitive to increasing the role of leadership, culture, and compensation. In the partial analysis, it is proven that the compensation factor is more dominant in influencing performance. This implies that maintaining performance requires many factors, especially compensation variables. The reason is that compensation is an instrument that has a major impact on the lives of employees, so the size of the change in compensation is closely related to the increase or decrease in performance.